Improved Sleep Quality and Sleep Duration After an 8-Week Exergaming Intervention for Exercise Training Among Elementary Schoolchildren in Taiwan - Hsiao-Fang Kao; Chi-Fang Lin; I-Tung Lin; Yi-Chuan Hung; Ting-Wei Chang; Chien-Chang Ho (Children)
Objectives: The present study aimed to investigate the effects of an 8-week exergaming intervention for exercise training on sleep quality and sleep duration among elementary schoolchildren in Taiwan. Methods: A randomized controlled trial design was employed, with 68 elementary schoolchildren (aged 10.76 ± 0.49 years) recruited and randomly assigned to either an experimental group (n = 35) or a control group (n = 33). The experimental group participated in an 8-week exergaming intervention for exercise training; this comprised three sessions per week consisting of three rounds per session, with each round lasting 1 min. The control group did not receive any training and maintained their regular daily routines. All participants provided information on their demographic characteristics and anthropometric measurements and completed the Pittsburgh Sleep Quality Index (PSQI) questionnaire at both pre-test (baseline) and post-test (week 8) assessments. Results: After 8 weeks of exergaming intervention, the experimental group showed a significant reduction in the PSQI global score (6.17 ± 2.96 vs. 4.80 ± 1.97, p < 0.0001). The change in the PSQI global score in the experimental group was significantly greater than in the control group (−1.37 ± 1.97 vs. −0.27 ± 1.89, p = 0.022). Additionally, the experimental group demonstrated a significantly longer sleep duration at week 8 compared with the control group (505.15 ± 53.16 vs. 480.51 ± 54.13, p = 0.047). Conclusions: Overall, the findings of this study indicate a beneficial response of elementary schoolchildren to exergaming, with participants reporting improved sleep quality and sleep duration as a result of engaging in the exergaming intervention sessions three times per week for 8 weeks, with three one-minute rounds per session. Therefore, it appears that exergaming may be an effective method for improving certain aspects of sleep quality and sleep duration among children between 10 and 12 years of age.